The results of a 12 month follow-up of an intravitreal dexamethasone implantation in persistent diabetic macular edema [Persistan diyabetik maküla ödeminde uygulanan vitre içi deksametazon implantasyonunun 12 Ay takip sonuçlar] - (:unkn) unknown (Gazi Eye Foundation, 2016)
Aim: To investigate the results of intravitreal dexamethasone implantation in patients with persistent diabetic macular edema despite anti- VEGF and photocoagulation treatment. Material and Method: The best corrected visual acuity, optical coherence tomography and intraocular pressure at 1st, 2nd, 3rd, 6th and 12th month follow-up in patients who had received grid/focal laser or more than three subsequent injections of anti-VEGF agents but had no improvement in best corrected visual acuity or had a central foveal thickness of >250 ?m were investigated. Results: The highest mean corrected best visual acuity gain and central foveal flattening was obtained at first month. At first and second months the mean best corrected visual acuity was significantly higher (p<.001, both) and also the mean central foveal thickness was significantly flatter. (p<.001, p=.016, correspondingly) Conclusion: Intravitreal anti-VEGF agents are effective and have relatively less side effects. Intravitreal dexamethazone implants on the other hand are successful in treating patients with persistent diabetic retinopathy who are otherwise unrespoinsive to other treatments and preferred injection interval might be 6 months. © 2016 Gazi Eye Foundation. All Rights Reserved.
Keywords: Diabetic maculopathy; Intravitreal dexamethasone implant; Ozurdex